Controle de Nematódas Gastrintestinais em Bovinos de Corte Utilizando Ivermectina Associada ao Fluazuron. - Bezerra, Jessica Silva Maia (Universidade Federal do Tocantins, 2023)
The supervised curricular internship was held from March 6, 2017 to May 12, 2017, at the private company Agroquima Produtos Agropecuários Ltda, a branch located in the city of Araguaína Tocantins, under the guidance of Professor Drª. Thássia Silva Reis and supervision of the Veterinary Doctor Rodrigo Dalcin Miotto, totaling a workload of 384 hours. The internship consisted in monitoring the various activities within the company, from sales follow-up, technical assistance and visits to properties for the purpose of diagnosing gastrointestinal nematodes from the active ingredient Ivermectin associated with Fluazuron, doing the Egg Count per Grass Of Feces (OPG) and coproculture. Fecal sample collection was performed on day 0 (zero) along with drug application, and the 21-day return on two properties and a 40-day return on a third property, a period in which a protocol was established For dementia and subsequent analysis of anthelmintic efficacy. And the importance of the Veterinarian also in the animal health sector guiding correctly the use of anthelmintic, and ensuring to the producer its effectiveness and consequently greater productivity.